2018
DOI: 10.1016/j.clnu.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hazelnut on serum lipid profile and fatty acid composition of erythrocyte phospholipids in children and adolescents with primary hyperlipidemia: A randomized controlled trial

Abstract: For the first time, we documented a positive effect of HZN consumption on lipid profile and FA composition of erythrocyte phospholipids in children with primary hyperlipidemia. Further studies are encouraged to better define HZN impact on the markers of CV risk in this population. The trial was registered under ISRCTN.com, ID no. ISRCTN12261900.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…However, the differences in fatty acid profile between small and large kernels were much less than the differences between macadamia cultivars [27,72,73] and between tree-nut species including almond, hazelnut, macadamia, pecan, pistachio and walnut [4,9]. All these nuts are considered beneficial for reducing the risk of cardiovascular disease because of their high levels of unsaturated fatty acids [1,2,7,10,14,[74][75][76][77][78][79]. Table 2.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…However, the differences in fatty acid profile between small and large kernels were much less than the differences between macadamia cultivars [27,72,73] and between tree-nut species including almond, hazelnut, macadamia, pecan, pistachio and walnut [4,9]. All these nuts are considered beneficial for reducing the risk of cardiovascular disease because of their high levels of unsaturated fatty acids [1,2,7,10,14,[74][75][76][77][78][79]. Table 2.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…To explore the role of tree nuts on lipid parameters within hyperlipidemic population, it was performed a systematic review of dose-response clinical trials 18-20 and controlled interventional trials. 20-46…”
Section: Methodsmentioning
confidence: 99%
“…Some findings indicated that hazelnuts exert a favorable impact on blood lipid concentrations. Deon et al 25 have noticed a significant reduction in LDL-c and elevation in HDL/LDL-c ratio after consuming hazelnuts either with skin or without skin (15-30 g/d) during a period of 8 weeks. Mercanligil et al 30 found that hazelnut has a lipid-lowering capacity, as they have observed that the daily inclusion of hazelnut (40 g) have a positive alteration in blood lipids among hypercholesterolemic men and thereby favorably influencing the coronary heart disease risk.…”
Section: Hazelnutmentioning
confidence: 99%
“…To ensure that this happened, each subject received 28 packets, each filled with a day’s ration of nuts, one for each day of the study. This regimen of nuts and number of nuts was devised based on previous studies with each of the following nuts [ 7 - 9 ].…”
Section: Methodsmentioning
confidence: 99%